ANALISA EFISIENSI ALAT PENGERING TENAGA SURYA TIPE TEROWONG BERBANTUKAN KIPAS ANGIN PADA PROSES PENGERINGAN BIJI KOPI - Ismet Eka Putra; Pitri Hadi (LP2M - Institut Teknologi Padang, 2013)
Coffee is a commodity of Indonesian plantations which accounts considerable for foreign exchange. Besides it, this effort involves the agricultural labor that quite high, which is more than 96% of Indonesian coffee plantations is managed traditionally by rural society, that are takes a long time to do it. To overcome these problems, so we designed and created a dryer that is solar dryers tunnel type. The purpose of this research was to determine the efficiency of the dryer. The dryer consists of spaces dryer, Solar collectors and ventilator. These dryers operate using solar energy and wind energy. In this research, the coffee beans are dried with initial moisture content of 59% as much as 29 kg. From results of this research obtained the efficiency of solar dryers tunnel type maximum 37%. The solar dryers tunnel type assisted fan, coffee beans dried until moisture content of 11% during 16 hours (2 days).